ADHD Symptomatology and Risky Health, Driving, and Financial Behaviors in College: The Mediating Role of Sensation Seeking and Effortful Control. (March 2015) - Graziano, Paulo A.; Reid, Adam; Slavec, Janine; Paneto, Adrian; McNamara, Joseph P.; Geffken, Gary R.
Objective: To examine the extent to which effortful control (EC) and sensation seeking (SS) tendencies explain the association between the severity of ADHD symptoms and risky behaviors.Method: Participants included 555 college students (66% females) who completed self-report measures assessing their ADHD symptoms, EC abilities, SS tendencies, and risky health (e.g., substance use) and driving/financial behaviors (e.g., misuse of credit cards).Results: Severity of college students' ADHD symptoms, EC abilities, and SS tendencies were related to all risky behaviors. Multiple mediational analyses further indicated that students' SS tendencies significantly mediated the association between ADHD symptoms and the risky health factor but not the risky driving/financial factor. EC, however, significantly mediated the association between ADHD symptoms and both the risky health and driving/financial factors.Conclusion: The current study provides initial data showing potentially different mechanisms that explain the link between college students' severity of ADHD symptoms and risky behaviors.